STUDY OF LISTERIA RESISTANCE IN FOOD PRODUCTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Listeriosis is a zoonotic bacterial infectious disease characterized by multiple sources of infection, a variety of pathways of transmission of the pathogen, polymorphism of clinical manifestations, and high mortality in newborns and people with immunodeficiency. The preservation of the viability of pathogenic microorganisms has a certain theoretical and practical significance in the hygienic assessment of environmental objects. The survival of microorganisms under various physical and chemical interactions may be important in the study of anthropogenic pollution of water bodies.